Representations of Islam in United States comics, 1880-1922 - Rhett, Maryanne A. (London ; New York)
xi, 183 sayfa
Keywords: “Representations of Islam in United States Comics, 1880-1922 examines the depiction of Islam, Muslims, and the Islamic world in U.S. popular culture, particularly comics and related artifacts, between 1880 and 1922. Through cartoons, comics, editorial cartoons, serialized advertisements and other materials the book unfolds a narrative about how the Islamic world and its people were understood by the American government and its people. This “knowledge,” garnered from popular culture of the day, produced a lens through which domestic and international relationships were created and maintained. Representing a wide swath of U.S. popular culture and discourse, the reflections these artifacts offer are united in their depiction of the “Oriental” in an era that is largely assumed to have been marked by American un-interest in the region, peoples and religion. An exciting contribution to a growing field, this book resituates the U.S. within the Islamic world, using the everyday medium of comics to provide a fresh perspective on the subject“ --